2022
DOI: 10.1084/jem.20211805
|View full text |Cite
|
Sign up to set email alerts
|

Ly49E separates liver ILC1s into embryo-derived and postnatal subsets with different functions

Abstract: Type 1 innate lymphoid cells (ILC1s) represent the predominant population of liver ILCs and function as important effectors and regulators of immune responses, but the cellular heterogeneity of ILC1s is not fully understood. Here, single-cell RNA sequencing and flow cytometric analysis demonstrated that liver ILC1s could be dissected into Ly49E+ and Ly49E− populations with unique transcriptional and phenotypic features. Genetic fate-mapping analysis revealed that liver Ly49E+ ILC1s with strong cytotoxicity ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 82 publications
5
34
0
Order By: Relevance
“…A previous study ( 56 ) showed that Ly49E − ILC1s up-regulate Ly49E in the liver after transfer into cNK/ILC1-deficient mice. Thus, Ly49E might be a marker not only for embryonic ILC1s ( 57 ) but also for a specific niche. After birth, embryonic ILC1s reduce their proliferative activity, consistent with an ongoing effector differentiation toward late, cytotoxic ILC1s, potentially allowing the second wave of neonatal helper-like ILC1s to colonize the liver.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study ( 56 ) showed that Ly49E − ILC1s up-regulate Ly49E in the liver after transfer into cNK/ILC1-deficient mice. Thus, Ly49E might be a marker not only for embryonic ILC1s ( 57 ) but also for a specific niche. After birth, embryonic ILC1s reduce their proliferative activity, consistent with an ongoing effector differentiation toward late, cytotoxic ILC1s, potentially allowing the second wave of neonatal helper-like ILC1s to colonize the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group [ 29 ] and others [ 34 , 44 ] have found murine Eomes −/lo ILC1 able to express perforin and granzyme A, B, and C and to kill target cells. Liver granzyme A + ILC1 are sensitive to Hobit deletion [ 30 , 44 ] and can originate from fetal ILC1 [ 107 ] or as a product of ILC3–ILC1 plasticity [ 29 ], but not from NK cells. In humans, a population of cytotoxic ILC1 was also found in the gut in conditions of IBD; this population is characterized by the expression of CD127, CD94, granulysin, and perforin and the presence of features of both CD127 + ILC1 and CD94 + NK cells [ 31 ].…”
Section: Nk Cells and The Expanding Family Of Cytotoxic Innate Lympho...mentioning
confidence: 99%
“…A recent study showed that hepatic ILC1s derived from different origins differ in their function [ 65 ]. By using inducible reporter mice to fate-map hematopoietic stem cells, but not lineage-restricted progenitors, the authors showed that a population of Ly49E + ILC1s was primarily fetus-derived and decreased with age, while Ly49E − ILC1s retained the ability to be replenished from adult progenitors.…”
Section: Origins Of Liver-resident Ilc1s and Nk Cellsmentioning
confidence: 99%
“…By using inducible reporter mice to fate-map hematopoietic stem cells, but not lineage-restricted progenitors, the authors showed that a population of Ly49E + ILC1s was primarily fetus-derived and decreased with age, while Ly49E − ILC1s retained the ability to be replenished from adult progenitors. Functionally, Ly49E + ILC1s expressed higher levels of granzymes and lysed target cells more efficiently in vitro, suggesting a distinct role for these fetus-derived cells in the host defense of neonates, whose adaptive immune system is not fully developed [ 65 ].…”
Section: Origins Of Liver-resident Ilc1s and Nk Cellsmentioning
confidence: 99%